2019
DOI: 10.3390/en13010160
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Nucleate Boiling of Flammable, Environmentally Friendly Refrigerants

Abstract: This paper investigates the nucleate boiling process of dimethyl ether and selected hydrocarbons. The main goal of this study is to measure the heat transfer coefficients of RE170, R600a, and R601, and to compare them with R134a. The experiments were carried out for heat fluxes up to 70 kW/m 2 . Experimental results have shown a typical trend that the heat transfer coefficient of flammable refrigerants increases as the heat flux increases. Among the tested fluids, the highest values of heat transfer coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…RE170 is a liquefied gas which is nontoxic, odourless and colourless at room temperature. The ozone depletion potential of dimethyl-ether is equal to zero and its global warming potential is significantly very low (GWP = 1) which have made it a potential green refrigerant to the environment [48].…”
Section: Characteristics and Chemical Composition Of The Investigated Refrigerantsmentioning
confidence: 99%
See 2 more Smart Citations
“…RE170 is a liquefied gas which is nontoxic, odourless and colourless at room temperature. The ozone depletion potential of dimethyl-ether is equal to zero and its global warming potential is significantly very low (GWP = 1) which have made it a potential green refrigerant to the environment [48].…”
Section: Characteristics and Chemical Composition Of The Investigated Refrigerantsmentioning
confidence: 99%
“…RE170 is produced from a variety of resources such as natural gas, biomass coal and methanol. Other components of R510A and R511A are hydrocarbons gasses (R600a and R290) and they are natural refrigerants generated as by-products in the production of natural gas [48]. The retail price or cost of refrigerants differs, with RE170 and its mixtures apt tending to cost less than conventional refrigerant (R134a).…”
Section: Availability and Cost Analysis Of The Studied Refrigerantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study evaluated the thermodynamic performance of DME refrigerant and R125, R134a, R143a, R152a, and R32 refrigerants. Although DME is a highly flammable substance, it has recently found reuse as a working fluid in cooling and heating systems due to its minimal GWP and zero ODP [14,15]. Ozone Depletion Potential (ODP) and Global Warming Potential (GWP) values and ASHRAE Safety Groups of the selected refrigerants are shared in Table 1.…”
Section: Selected Refrigerantsmentioning
confidence: 99%
“…In summary, a renewable hydrate guest with stable chemical properties, nontoxic, no ozone depletion potential (ODP), a low GWP, a low price, and a wide source is still the focus of future research. , It is found that dimethyl ether (DME, RE170) is widely studied as an environment-friendly (ODP = 0, GWP <3, which is only 1/500 of HFCs) and effective refrigerant, which can be easily produced from renewable energy (biomass). , Moreover, it can significantly lower pressures under the same conditions than CO 2 with a low saturated vapor pressure, which is expected to reduce the operating pressure of the gas hydrate as a cold storage medium or refrigerant. However, there is still a lack of DME gas hydrate phase equilibrium data at low pressure and suitable temperature with these additives.…”
Section: Introductionmentioning
confidence: 99%